1994
DOI: 10.1590/s0074-02761994000300018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study on experimental infection of rotavirus in a murine heterologous model

Abstract: Viral replication, histopathological and ultrastructural changes were observed for a period of nine days in the small intestine of suckling mice infected with a simian rotavirus (SA11). Samples taken from duodenum, jejunum and ileum were prepared for light microscopy, transmission and scanning electron microscopy analysis. Histopathologic effect could be detected within 8 hr post-infection, when only a few altered cells were observed. Damage was extensive after 16 hr post-infection, showing swollen enterocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…We therefore chose the RRV mouse-infection model to test the activity of the lactobodies. Although it is a heterologous pathogen, the infection of mice with the simian SA11 rotavirus strain leads to pathophysiological alterations that are characteristic of rotavirus infection in humans [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore chose the RRV mouse-infection model to test the activity of the lactobodies. Although it is a heterologous pathogen, the infection of mice with the simian SA11 rotavirus strain leads to pathophysiological alterations that are characteristic of rotavirus infection in humans [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Kubelka et al (17) have observed more changes in the jejunum in SA11-infected mice. Others have demonstrated similar changes in the ileum and jejunum in SA11-infected mice (18) or in group B rotavirusinfected rats (24). Heyman et al (13) have reported the appearance of vacuoles in enterocytes of the villi of the proximal small intestine associated with a release of mucus in the lumen of mice infected with a murine strain.…”
mentioning
confidence: 89%
“…However, difficulties in growing murine rotavirus strains to high concentrations in tissue culture have limited their use (21). The use of heterologous rotavirus, particularly the simian SA11, strain, has led to physiopathological symptoms in mice identical to those produced by the murine strain (3,17,18,21) and may limit cross contamination among animals bred in the laboratory (6).…”
mentioning
confidence: 99%
“…These differences have been attributed to the specific nature of the host response and not to the virus, since vacuolization is also a characteristic feature of heterologous infections in mice (2,19,38). Mice usually do not develop any symptoms beyond 2 weeks of age, and infection of adult mice occurs without disease or histopathological lesions (7,18,43,46,61,67).…”
mentioning
confidence: 99%